Penerapan Kesehatan dan Keselamatan Kerja dengan Metode Hazard Operability Study di Industri Mebel Kabupaten Sukoharjo - Fery Wisnu Saputro; Tri Wisudawati; Wahyu Adhi Saputro (Universitas Medan Area, 2022)
The furniture industry is one of the largest industries in Sukoharjo Regency. Indeed, this industry is able to penetrate the international market share so that it has great potential. Behind this great potential, it is possible that there are potential hazards and work risks that arise in the manufacture of furniture. This study aims to determine the application of occupational health and safety in the furniture industry in Sukoharjo Regency. This research uses data analysis method with hazard operability study method. Based on the results of the study stated that there are five stages of work in the furniture industry in Sukoharjo Regency. The first step is sanding and then painting. The third stage is followed by drying and drying then packing and the last is the transportation of goods. Based on the results of the study, it can be seen that the potential for extreme work hazards is 10%, low risk is 40% and the rest is moderate and high risk.